Employer expectations toward accounting graduates’ soft skills in Malaysia - Chew, Sabrina Hui Xin; Ye, Simin; Ooi, Wan Cing; Tan, Sze Ying; Yeoh, Jian Sian (2020)
As a kind of high-quality human capital, professional accountants are an important prerequisite and condition for a country's sustainable development. Malaysia needs more professional accountants, and accounting firms are constantly seeking for capable accounting graduates to maintain their competitive edge, thus this study stresses on the quality and employability of accounting graduates. However, there is a gap exists between employers and accounting graduates on the perceptions of soft skills required. Besides, undergraduate business education seems to place too much emphasis on academicism, neglecting to provide students with soft skills training, which is insufficient to meet the expectation of employers. Therefore, our study aims to analyse the employers’ expectations on soft skills toward accounting graduates in Malaysia, thereby enhancing the employability and competitiveness of accounting graduates, and providing a reference for the curriculum setting towards accounting graduates in colleges and universities. Throughout this study, we investigated the correlation between employer expectation and the independent variables of communication skill, teamwork skill, problem solving skill and ethics. We prepared 110 sets of questionnaire and distributed them to the managers in the registered accounting firms in Malaysia. Thereafter, Statistical Package for the Social Sciences (SPSS) is conducted to test the data and generate the results. The findings indicates that the independent variables (communication skill, teamwork skill, problem solving skill and ethics) are significantly correlated with the dependent variables (employer expectations), and there is a positive correlation between them. In addition, the relative importance of respective independent variables in explaining employer expectations was analysed.